1981
DOI: 10.1159/000250253
|View full text |Cite
|
Sign up to set email alerts
|

Tinea versicolor: Ultrastructural Studies on Hypopigmented and Hyperpigmented Skin

Abstract: Punch biopsy specimens from 4 patients with confirmed diagnosis of tinea versicolor were investigated. Hypopigmented, hyperigmented and uninvolved sites from the same subject were compared in relation to ultrastructural alterations as a result of infection with Malassezia furfur, by light, scanning, and transmission electron microscopy. Hyperpigmented skin had thicker stratum corneum than hypopigmented but both were thicker than the uninvolved skin. A large number of tonofilaments were noticed in hyperpigmente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…Several theories have been proposed to explain hypopigmentation, including the filtering of UV light by the growth of the organism in the skin (14), a block in the transfer of melanosomes to keratinocytes (14,89,121,153,208), and the inhibition of melanin production by azelaic acid (180,302) or by lipoxygenase (304). Other groups have suggested that the hyperpigmentation of lesions was due to inflammation (116,153), increased skin thickness, or larger numbers of organisms in the skin (153).…”
Section: Pityriasis Versicolormentioning
confidence: 99%
“…Several theories have been proposed to explain hypopigmentation, including the filtering of UV light by the growth of the organism in the skin (14), a block in the transfer of melanosomes to keratinocytes (14,89,121,153,208), and the inhibition of melanin production by azelaic acid (180,302) or by lipoxygenase (304). Other groups have suggested that the hyperpigmentation of lesions was due to inflammation (116,153), increased skin thickness, or larger numbers of organisms in the skin (153).…”
Section: Pityriasis Versicolormentioning
confidence: 99%
“…Depigmentation occurs frequently in affected areas, causing a pronounced loss of melanin even after successful antimycotic therapy. Histopathological and ultrastructural examinations of the lesions have led to somewhat contradictory findings, such as decreased numbers of melanosomes [8] and melanocytes, [9] disturbed transport of melanosomes to keratinocytes, [10] and morphological changes in melanocytes that were ascribed to toxic influences. [11,12] This prompted us to investigate the influence of Malassezia alkaloids on cultured primary human melanocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The hypopigmentation is related to dicarboxylic acids produced by fungi that may inhibit the dopa-tyrosine reaction that produces host melanin [22]. According to Karaoui, melanocyte damage also is caused by fungi, varying from altered melanosomes, damage to mitochondria to actual degeneration [23]. The size and distribution of melanosomes can be different between patients: when the melanosomes are abnormally small hypopigmentation occurs, while when the melanosomes are extra-large hyperpigmentation appears [22].…”
Section: Dermatophytosismentioning
confidence: 99%